ANALISIS PENERAPAN FULL COSTING DENGAN METODE HARGA POKOK PESANAN DALAM MENENTUKAN HPP(Studi Kasus AlFalah Cake) - Siti Nur Haliszah; Nur Hamidatul Ulfiyanah, Dewi Agustya Ningrum, Darno, Eko Purwanto (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2024)
MSMEs play an important role in Indonesia's economic development and labor training arising from production and sales activities. Snack cakes are famous for equalizing Indonesia's development and have spread throughout the country. The purpose of this study is to estimate production costs using excel for ALFALAH CAKE MSMEs by taking into account general acceptance standards and the specific characteristics of these MSMEs and using full costing with the order costing method. This article uses descriptive research with quantitative data analysis. In designing this calculation, several procedures are carried out, namely: 1. Determine input data, 2. Determine raw material costs, 3. Determine direct labor costs and overhead costs